Pulmonary Nodules as an Initial Manifestation of Behçet’s Disease - M. Malekmohammad; A. Emamifar (Case Reports in Rheumatology)
Behçet’s disease (BD) is a systemic vasculopathy, characterized by recurrent oral aphthae, genital ulcers, uveitis, and skin lesions. Although vascular involvement, including venous and arteries of any size, is a usual manifestation, cases with pulmonary thrombosis as the initial symptom are not common in the absence of pulmonary artery aneurysm (PAA). This report describes a 36-year-old man with recurrent fever, nonmassive hemoptysis, and persistent cough with lung nodules in CT scan who had undergone open lung biopsy. On the basis of morphological findings, BD was suggested and more precise evaluation confirmed the diagnosis.